-6u+3=-3(u-3)

Simple and best practice solution for -6u+3=-3(u-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6u+3=-3(u-3) equation:


Simplifying
-6u + 3 = -3(u + -3)

Reorder the terms:
3 + -6u = -3(u + -3)

Reorder the terms:
3 + -6u = -3(-3 + u)
3 + -6u = (-3 * -3 + u * -3)
3 + -6u = (9 + -3u)

Solving
3 + -6u = 9 + -3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '3u' to each side of the equation.
3 + -6u + 3u = 9 + -3u + 3u

Combine like terms: -6u + 3u = -3u
3 + -3u = 9 + -3u + 3u

Combine like terms: -3u + 3u = 0
3 + -3u = 9 + 0
3 + -3u = 9

Add '-3' to each side of the equation.
3 + -3 + -3u = 9 + -3

Combine like terms: 3 + -3 = 0
0 + -3u = 9 + -3
-3u = 9 + -3

Combine like terms: 9 + -3 = 6
-3u = 6

Divide each side by '-3'.
u = -2

Simplifying
u = -2

See similar equations:

| 6sen(A)-3=0 | | -3m=-4+8 | | a^2+11a+10=0 | | (6d+5)(d-8)= | | X/5=12/35 | | 28x^2-94x+60=0 | | 28x^2-94x+30=0 | | (3c^2+2c-1)(2c^2+c+9)= | | xy-2a-2x+ay= | | 3x^2+9x-1= | | (3c+2c-1)(2c^2+c+9)= | | 3a^2+6a+2=0 | | 3u^3+15u^2-87u-315=0 | | -10.8/-2= | | 4+3(3a+3)=5 | | 0.01x-1.5=0.009 | | 3.14*R^2*12=258.75 | | pi*r^2*12=258.75 | | 1/10x-1/15=-1/6 | | 4/38x27/8 | | 7/9*n=7/10 | | -10.8/(-2)= | | y=x+6x+8 | | (5x)(3x^2y)(2yz)=0 | | 1/3(d=9)=-12 | | (23-1v)/10=-6 | | 3*(-4)*(-4)*(-1)= | | 4(w-5)-6w=-8 | | 1/n=1/(5n)-(n-1)/(5n) | | t-6t-5=-4 | | (23-v)/10=-6 | | cos^2x-sin^2x=sinx |

Equations solver categories